Menurunkan Tekanan Darah pada Lansia dengan Hipertensi melalui SEFT - Ros Endah Happy Patriyani; Dwi Sulistyowati (Poltekkes Kemenkes Surakarta, 2020)
Background: Increased high blood pressure in the elderly can be caused by various factors, one of which is stress. Stress can trigger the onset of hypertension through activation of the sympathetic nervous system which causes an increase in blood pressure intermittently. Hypertension patients need to be helped to reduce stress so that blood pressure does not increase. One of the non-pharmacological therapies to reduce stress is SEFT therapy. The purpose of this activity are to increase the elderly's knowledge about hypertension and increase awareness to control blood pressure and lowering blood pressure with SEFT therapy. Methods: Method this study is used blood pressure measurement, health education, and SEFT therapy. Results: Of this activity are health education can increase knowledge and awareness in controlling blood pressure, and SEFT therapy can reduce blood pressure in elderly hypertension. Conclusion: SEFT therapy can be an intervention alternative in reducing blood pressure.